Drivers of winter ice formation on Arctic water bodies in the Lena Delta, Siberia - Martha Lütjen; Pier Paul Overduin; Bennet Juhls; Julia Boike; Anne Morgenstern; Hanno Meyer (Arctic, Antarctic, and Alpine Research)
Arctic landscapes are characterized by diverse water bodies, which are covered with ice for most of the year. Ice controls surface albedo, hydrological properties, gas exchange, and ecosystem services, but freezing processes differ between water bodies. We studied the influence of geomorphology and meteorology on winter ice of water bodies in the Lena Delta, Siberia. Electrical conductivity (EC) and stable water isotopes of ice cores from four winters and six water bodies were measured at unprecedented resolution down to 2-cm increments, revealing differences in freezing systems. Open-system freezing shows near-constant isotopic and EC gradients in ice, whereas closed-system freezing shows decreasing isotopic composition with depth. Lena River ice displays three zones of isotopic composition within the ice, reflecting open-system freezing that records changing water sources over the winter. The isotope composition of ice covers in landscape units of different ages also reflects the individual water reservoir settings (i.e., Pleistocene vs. Holocene ground ice thaw). Ice growth models indicate that snow properties are a dominant determinant of ice growth over winter. Our findings provide novel insights into the winter hydrochemistry of Arctic ice covers, including the influences of meteorology and water body geomorphology on freezing rates and processes.